Methods of detecting defects in radio electronic devices - Abdugafur Khotamov; Tulkin Sultonov (International Journal on Orange Technologies, 2022)
With the increase in the number of electronic devices, their tasks became more complex, and the range of services provided increased. Many radio tools must work together to provide one or more services. Accordingly, interference in the radiation radio receiver interferes with the correct reception of the signal, affects the circuit of the radio receiver, and also violates the signals during transmission of radio waves. The article discusses the causes and causes of problems arising from electromagnetic interference in most communication facilities, industry and industry of the republic.